Antibiotic Resistance Patterns of Salmonella Typhi and Non-Typhi in North-Central Nigeria: A Cross-Sectional Study - Bimba, John S; Wudiri, Zara; Okohu, Isaac; Okafor, Kingsley; Lucy, Idoko; Lawson, Lovett; Cuevas, Luis E. (British Journal of Healthcare and Medical Research, 2024)
Antimicrobial resistance significantly threatens global health, especially in treating Salmonella infections in developing countries. In sub-Saharan Africa, inadequate water, sanitation, and limited diagnostic and treatment capabilities exacerbate the issue. This study addresses the lack of data on enteric fever and drug susceptibility patterns of Salmonella in Nigeria. The objective of the study was to identify Salmonella isolates from febrile patients in Karu Local Government Area, Nasarawa State, Nigeria, and determine their antibiotic resistance patterns. Secondary objectives included characterizing the demographics and clinical profiles of infected patients. This cross-sectional study was conducted in four health facilities. Research assistants recruited individuals clinically diagnosed with enteric fever and with temperatures above 37.4°C. Blood samples were collected and cultured using the BD Bactec™ FX automated system. Isolates were identified through morphology, Gram stain, and chemical methods. Antibiotic susceptibility was tested using the modified Kirby-Bauer method, interpreted per CLSI guidelines. The data was analyzed using Statistical package for the Social Sciences (version 24) The results showed out of 818 febrile patients, bacterial pathogens were isolated in 46 cases (5.6%). The majority were gram-negative bacteria, with Salmonella spp. leading (43.5%). Salmonella Typhi accounted for 23.9%, and non-Typhi Salmonella 19.6%. Both S. Typhi and non-Typhi Salmonella showed over 60% resistance to Trimethoprim/Sulfamethoxazole and chloramphenicol. Cephalosporin resistance was also high, whereas fluoroquinolone resistance was low. Notably, interesting resistance patterns were observed to Imipenem, Streptomycin, and Gentamicin. The study highlights the high prevalence of Salmonella infections and significant antibiotic resistance in the region. Health facilities can enhance diagnostic capabilities, routine antimicrobial surveillance, and antibiotic stewardship. Health authorities and communities should partner to improving water, hygiene, sanitation, to mitigate the impact of these infections and combat antimicrobial resistance.